Sensing Material Temperature Effect on the Multiple Gas Sensor Sensing Response - Anze Sitar; Elia Scattolo; Matteo Valt; Alvise Bagolini; Pietro Tosato; Andrea Gaiardo (Proceedings)
The temperature of the sensing material has a large impact on the tin-oxide gas sensor performance. However, the thermal analysis of gas sensors is often overlooked or only partially included in the studies. The aim of this research was to employ numerical simulations to investigate the temperature effect on the detection of the ethanol in an ethanol/air mixture by positioning multiple electrodes on a single heated membrane. The experimental results validated the electrothermal simulation and indicated a significant temperature effect on the sensor responsivity. Indeed, the decrease in the average sensor temperature from 427 °C to 411 °C increased the sensing response by approximately 75 % during the 5 ppm ethanol mixture flow over the sensor array.